TEACHERS’ STRATEGY IN TEACHING WRITING BY ONLINE APPLICATION AT MTS N 2 MEDAN - Fauziah Tambak; Indra Hartoyo (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
This study discusses the strategies that teachers use when learning through online applications. This investigation raises the main problem, namely "what strategy is used by the teacher". The purpose of this study was investigate what types of strategies used by teachers in learning to write through online applications at MTs N 2 Medan. This research was conducted in class eight and nine grade at MTs N 2 Medan. This study used a qualitative descriptive method and collected data through documentation and interviews. The framework proposed by Hamruni (2011). The Analyze data in four steps: 1). Data Collection, 2) Data Condensation, 3) Data Display, 4) Conclusion and Drawing / Verification. Applications carried out by researchers at school use the Whatsapp application. Based on the findings, there are three strategies used by the two teachers when teaching online at MTs N 2 Medan. Namely, direct teaching strategies, cooperative learning strategies and problem-based strategies. Although not very specific, with theory, it can be said that the two teachers used three of the four theories. Although not very specific, with theory, it can be said that the two teachers used three of the four theories. In addition, the researcher also found that teachers at MTs N 2 Medan taught using descriptive text, where there were 4 types of teaching processes used by teachers through online applications, namely namely, Planning, Drafting, Editing and Final Version for teacher A, and Planning, Compilation, Editing, Final Version.Keywords: Teacher, Strategy, Teaching, Writing, application.